2020
DOI: 10.1186/s12931-020-01518-6
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CXCR7 accelerates tumor growth and metastasis of lung cancer cells

Abstract: Background Under physiological conditions, CXCL12 modulates cell proliferation, survival, angiogenesis, and migration mainly through CXCR4. Interestingly, the newly discovered receptor CXCR7 for CXCL12 is highly expressed in many tumor cells as well as tumor-associated blood vessels, although the level of CXCR7 in normal cells is low. Recently, many studies have suggested that CXCR7 promotes cell growth and metastasis in more than 20 human malignancies, among which lung cancer is the leading cause of cancer-as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…CXCL12 likely promotes glycolytic metabolism through other processes activated by CXCL12 signaling through CXCR4 and/or ACKR3, including ERK and Akt. Collectively, these, and potentially other CXCL12-dependent pathways, support the increased proliferation of cancer cells previously reported by our group and others [ 12 , 13 , 48 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 89%
“…CXCL12 likely promotes glycolytic metabolism through other processes activated by CXCL12 signaling through CXCR4 and/or ACKR3, including ERK and Akt. Collectively, these, and potentially other CXCL12-dependent pathways, support the increased proliferation of cancer cells previously reported by our group and others [ 12 , 13 , 48 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 89%
“…SDF-1, also known as Chemokine 12 (CXCL12) is ubiquitously expressed in many tissues and cell types, and it can speci cally interact with the ligand for CXCR4 [16]. In clinical LC samples, CXCR4 is highly expressed in both normal and tumor tissues [17]. The CXCL12/SDF-1 and its receptor CXCR4 play a major role in tumor initiation, promotion, progression and metastasis [12,13,18].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have revealed that hsa_circ_0072309 is significantly overexpressed in human NSCLC tissues when compared to matching normal samples and elevated in A549 LC cells when compared to BEAS‐2B normal lung cells, where it promotes NSCLC cell proliferation, migration, and invasion while inhibits apoptosis 42,43 . Similarly, CXCR7 (ACKR3) is overexpressed in lung tumor tissues, and upregulation of CXCR7 markedly promotes A549 cell migration in vitro and enhances tumor growth and metastasis in vivo 44,45 . In contrast, miR‐100 is substantially downregulated in NSCLC tissues, and miR‐100 restoration can inhibit the formation of tumors, the advancement of the G2/M cell cycle, and the proliferation, invasion, and migration of NSCLC cells 20,46,47 .…”
Section: Discussionmentioning
confidence: 99%